Influence of dry ports construction on seaport growth: Case of Ningbo Zhoushan Port. (March 2022) - Wan, Shulin; Luan, Weixin; Chen, Yuying; Lin, Qiaoqiao
Abstract: Despite the vigorous development of dry ports, there is a lack of evaluation on the practical effects of dry port projects. Considering Ningbo Zhoushan Port as an example, this study employs a Difference-in-Differences approach to investigate the effect of dry port construction on the growth of seaports in China. China Customs foreign trade container data and Chinese prefecture-level city panel data are utilized in this study. Further, the mediation model is used to investigate the impact mechanism of dry port construction on city-port container flows. The findings show that the construction of the dry port has significantly promoted the growth of the city-port container volume, which has increased by 31.5%. Such an impact depends on foreign trade growth and port substitution effects. Thus, the results provide support to the government and port stakeholders in clarifying the benefits and influence channels of dry port construction, ultimately promoting port growth and inland economic development. Highlights: The influence of dry ports construction on seaport growth is examined. The case of Ningbo Zhoushan Port, China is addressed. DID analysis is conducted to assess the causal impact of the dry port. Dry ports promote the growth of city-port container volumes. Foreign trade growth and port substitution effects mediate this growth.